Historical Evolution of the Regulation of Criminal Registration (1884 – 2020) - Markov, Pressiyan (Research Papers, 2021)
The paper is aimed at establishing the tendencies in the regulation of criminal registration by using the comparative historical method of research. The Conviction Registration Service was established in 1904. Since then to present day more and more data about convicts are collected and stored. Although necessary for the due criminal justice process, two negative tendencies arise: there is an exponential growth in the number and duration of collateral consequences, and in the persons, who are allowed to access the conviction data. That is why criminal registration must be considered main consequence of conviction as it ensures the possibility to enforce all other collateral consequences.